CONTENTS (The Strategic Review for Southern Africa, 2020)
From the EditorHenning Melber ................................................................................................................. 1Knowledge production and decolonisation — not only African challenges Henning Melber................................................................................................................... 4
Keywords: Knowledge production; decolonisation; epistemological decolonisation; epistemic freedom; feminist posthumanism; colonial nature and universities; Decolonising the university